Cooking the Cuban way : culturally authentic foods, including low-fat and vegetarian recipes / Alison Behnke; Victor Manuel Valens - Behnke, Alison
An introduction to Cuban cooking featuring traditional recipes for yucca with garlic sauce, creole chicken, mango and papaya milkshake. Also includes information on the history, geography, customs, and people of this Caribbean island nation.